IMPACT OF Conocarpus erectus L. FERTILIZER, AND SOME MICRONUTRIENTS ON GROWTH AND PRODUCTION OF POTATO - & Al-Amri, Al-Dulaimi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to determine the impact of Conocarpus erectus L. compost fertilizer, and some micronutrients on growth and production of potato. This research was conducted at one of the fields of the College of Agricultural Engineering Sciences - University of Baghdad. The experiment was implemented using factorial arrangement (4X3X3) within randomized complete block design with three replicates. Conocarpus fertilizer was represented the first factor with three levels (7.5, 15, 30 ton.ha-1), which symbolized (C2, C3, C4). Chemical fertilizer as recommended dose as a control, which symbolized (C1). The second factor was foliar spraying with three levels of iron (0, 100, 200 mg.L-1), which symbolized (F0, F1, F2). The third factor is foliar spraying with three levels of boron (0, 50, 100 mg.L-1), which symbolized (B0, B1, B2). The statistical analysis showed superiority of C3 in producing significant values of the studied traits such as, leaf area (154.77,  187.93 dcm2) for fall and spring seasons respectively, plant yield (649.7 gm.) for fall season only. Also the results revealed the significant impact of F2 treatment in producing high leaf area (153.63,  177.22 dcm2) for fall and spring seasons respectively. B2 treatment demonstrated significant values in producing high starch percentage (10.09%, 10.85%) for fall and spring seasons respectively, The results that obtained from triple interaction exhibited significant superiority of treatments C1F1B2 and C3F2B0 in producing the highest plant yield (811 g,  1239.2 g.) for both seasons respectively.